2019
DOI: 10.1101/734699
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Secretomes of Painful Versus Nonpainful Human Schwannomatosis Tumor Cells Differentially Influence Sensory Neuron Gene Expression and Sensitivity

Abstract: Schwannomatosis is a multiple tumor syndrome in which patients develop benign tumors along peripheral nerves throughout the body. The first symptom with which schwannomatosis patients often present, prior to discovery of tumors, is pain. This pain can be debilitating and is often inadequately alleviated by pharmacological approaches. Schwannomatosis-associated pain can be localized to the area of a tumor, or widespread. Moreover, not all tumors are painful, and the occurrence of pain is often unrelated to tumo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 59 publications
(26 reference statements)
0
12
0
Order By: Relevance
“…Our prior study focused on deciphering the molecular mechanisms of painful tumors (Pain score >7) compared to "non-painful" tumors (pain score <3) [10]. Those in vitro experiments revealed that CM collected from painful SWN tumors, but not that from nonpainful SWN tumors, contained increased amounts of multiple cytokines, upregulated the expression of pain-associated genes in sensory neuron cultures, and increased neuronal responses to noxious TRPV1 and TRPA1 agonists [10]. In the present study, these and additional CM samples were injected in vivo to assess whether the secretome of SWN cells can induce painful behaviors in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Our prior study focused on deciphering the molecular mechanisms of painful tumors (Pain score >7) compared to "non-painful" tumors (pain score <3) [10]. Those in vitro experiments revealed that CM collected from painful SWN tumors, but not that from nonpainful SWN tumors, contained increased amounts of multiple cytokines, upregulated the expression of pain-associated genes in sensory neuron cultures, and increased neuronal responses to noxious TRPV1 and TRPA1 agonists [10]. In the present study, these and additional CM samples were injected in vivo to assess whether the secretome of SWN cells can induce painful behaviors in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Ding et al [10] suggest that the structural and functional abnormalities of the SMARCB1 gene might be the molecular basis of familial schwannomatosis. If the focus involves peripheral-nerve tissue, it can be accompanied by pain [11]. Jordan et al [12], using a simple 10-point pain scale (SF-36) to explore the relationship between pain and mutation of the SMARCB1 and LZTR1 genes in schwannomatosis, found that the median pain score of the LZTR1 group was 3.9 and that of the SMARCB1 group was 0.5 (P = 0.0414).…”
Section: Discussionmentioning
confidence: 99%
“…Painful tumors in schwannomatosis secrete factors that act on nearby nerves to augment nociception by producing neuronal sensitization or spontaneous neuronal firing, as evidenced by the work done in cell lines of painful and non‐painful tumors (Ostrow et al, 2019). Increased sensitivity to depolarization by KCl, increased response to noxious TRPV1 and TRPA1 agonists, and upregulation of pain‐associated gene expression were found in the DRG cultures (Ostrow et al, 2019). In 7q11.23 duplication syndrome, one‐fourth of parents reported high pain tolerance in their affected children (Morris et al, 2015).…”
Section: Discussionmentioning
confidence: 99%